The Phenomenon of Coastal Women: Between Patriarchal Culture and Gender Justice - Misrina, Misrina (Peneliti.net, 2024)
Presently, there is a new phenomenon of empowering women in areas still strong with customs and traditions. Similarly, the dynamics of women policy democratization have experienced gaps in a multicultural society historically categorized as the Islamic Kingdom's territory. Therefore, the government is faced with the challenge of determining the right strategies to align cultural structures that have lived in society for a long time using inclusive programs. These included activities to empower coastal women in the economic sector to improve the welfare of the community. This study aims to analyze the phenomenon of social anthropology in the democracy era. It fills the gap associated with the various failures in implementing various programs by prioritizing gender justice and equality in patriarchal remote areas with the character of an Islamic sultanate.